ANIMATED FILMS AS CREATIVITY STIMULUS MEDIA TO DRAW ILLUSTRATIONS FOR CLASS III B STUDENTS OF SEMESTA BILINGUAL ELEMENTARY SCHOOL - sari, Yofita; Jazuli, Muhammad; Syakir, Syakir (Universitas Negeri Semarang, 2019)
The plethora of emerging technology or the rapid development of civilization will require for readiness of the human resources which are more creative in every aspect. Hence creative environmental conditions and the availability of opportunities to carry out various creative activities for children need to be utilized to develop their culture of creativity. This study aims to analyze the creativity of students as a result of utilizing animated films in drawing illustrations. This is a qualitative research with controlled observation. The research location is in the Semesta Bilingual Elementary School with the third grade students as the subjects. Data collection techniques used are observation, interview, documentation, and test which are validated by using data triangulation. Data analysis techniques are carried out qualitatively and quantitatively by using aesthetic and creativity theories. The results of the study show that based on aesthetic aspects on controlled observation 1, most of the students (50%) got the score 75-80 of fair category; while on the controlled observation 2, most of the students (43.75%) got a score range 81-85 of good category. Meanwhile, based on the creativity aspect of the 16 students of Class III B, five students (31.25%) choose the S-01 scene, two students (12.5%) chosse the S-02 scene, four students (25%) choose the S-03 scene, three students (18.75%) choose the S-04 scene, and two students (12.5%) choose the S-05 scene as a reference to draw the illustration of Finding Nemo. The creativity analysis shows that students start by taking the references from the scenes, developing ideas in creating the works by adding fish figures and other objects, as well as beautifying the background with gradation coloring technique. The final results obtained indicate an improvement in students’ creativity. Animated films can attract students' attention, optimize students' ability, and stimulate students' creativity in creating works. This study is expected to be able to develop the students’ potential to think and be creative in facing the rapid development of technology.